PENGARUH LATIHAN TEKNIK MENGGIRING LURUS/STRAIGHT LINE TERHADAP KEMAMPUAN DRIBBLING SEPAKBOLA TIM EKSTRAKULIKULER SMAN 1 BANGKINANG - Ahyatul Khairi; Vigi Indah Permatha Sari; Iska Noviardila (LPPM - Universitas Pahlawan Tuanku Tambusai, 2023)
This research is based on field observations based on the fact that the Extracurricular Team at SMAN 1 Bangkinang was unable to dribbling well. The aim of this research is to find out how much influence straight dribbling technique training has on the soccer dribbling ability of the SMAN 1 Bangkinang extracurricular team. This research method is an experimental method. The research was carried out at SMAN 1 Bangkinang in January 2024. The sample for this research was the entire extracurricular team of SMAN 1 Bangkinang, namely 18 students. To measure football dribbling ability by carrying out a dribbling test. The results of the research were